Development Of Pedagogical Design Elements For The My Arabiy Game-X Model To Enhance Arabic Language Learning In Religious Primary Schools - Mohamed Masrop, Noor Azli; Zainuddin, Ghazali; Ramlan, Siti Rosilawati; Sahrir, Muhammad Sabri; Ismail, Irwan Mahazir; Adnan, Ahmad Syukri; Muslil, Yuszaimi; Md Yusof, Md Ridzal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The use of teaching aids in Arabic language instruction has shown positive effects on students’ vocabulary acquisition. However, many teachers still do not fully utilize technology and teaching materials in the teaching and learning process. Therefore, this study developed the My Arabiy Game-X model as a guide for creating interactive and user-friendly mobile applications to support Arabic language teaching in religious primary schools. The study focused on three of the seven primary constructs related to pedagogical design: teacher needs, learning objectives, and assessment of learning outcomes. The Fuzzy Delphi Method (FDM) was used in a structured way to ensure the accuracy and validity of the data. A total of 22 experts were selected through purposive sampling, including those with expertise in curriculum, teaching, educational technology, multimedia, information technology, and assessment. The research instrument was a questionnaire developed from a literature review and expert interviews. Data were analyzed using a Microsoft Excel template. Findings showed that all elements within the three constructs reached consensus among the experts. The pedagogical design of the model has strong potential as a helpful guide for developing more holistic, relevant, and effective Arabic language learning apps, in line with 21st-century educational digitalization initiatives.